Ювілей А. В. Риндич (Биополимеры и клетка, 1999)
18 січня
1999
року
виповнилося
60
років
з
дня
народження
та
35
років
наукової
діяльності
Алли
Володимирівни
Риндич
—
знаного
фахівця
в
галузі
молекулярної
біології
та
онкогенетики,
члена-кореспондента
HAH
України,
доктора
біологічних
наук,
професора,
завідувача
відділу
молекулярної
онкогенетики
Інституту
молекулярної
біології
і генетики
HAH
України.